Mengukur Efektivitas Social Media Bagi Perusahaan - Kuspuji Catur Bagus Wicaksono (Binus Business Review, 2013)
Enterprises have a new tool in conducting marketing activities to reach more targeted consumers, which is social media. Social media provides a wide range of alternatives for entrepreneurs and companies in conducting marketing activities, which has more interaction and more social to consumers. However, in doing so it is not carelessly, because it must take into consideration the use of measurement and the benefits that would be obtained by using social media. Recently, there are many existing measurements. However, along with the development of the information technology, means to do marketing have to develop also.